2009
DOI: 10.1007/s10549-009-0461-7
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of HER2 status between primary tumors and corresponding circulating tumor cells in advanced breast cancer patients

Abstract: Biocharacterization of circulating tumor cells (CTCs) in the peripheral blood of advanced breast cancer (ABC) patients may represent a real-time tumor biopsy. We assessed HER2 status on CTCs from blood samples of ABC patients. CTCs were separated and stained using the CellSearch System Ò . HER2 status was assessed by immunofluorescence and, when technically feasible, by fluorescence in situ hybridization. Blood samples were obtained from 66 ABC patients. Forty patients had a positive CTC sample (61%) and of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
131
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(147 citation statements)
references
References 36 publications
(60 reference statements)
14
131
0
2
Order By: Relevance
“…Nevertheless, such discrepancies between the levels of ER and HER2 measured in the primary tumor and metastases and CTCs have been described before at both the mRNA and the protein level (40,45,(48)(49)(50)(51), indicating that the findings with our multigene measuring technique may indeed be relevant, not only for ER and HER2 but also for the other markers included in our panel.…”
Section: Discussionmentioning
confidence: 62%
“…Nevertheless, such discrepancies between the levels of ER and HER2 measured in the primary tumor and metastases and CTCs have been described before at both the mRNA and the protein level (40,45,(48)(49)(50)(51), indicating that the findings with our multigene measuring technique may indeed be relevant, not only for ER and HER2 but also for the other markers included in our panel.…”
Section: Discussionmentioning
confidence: 62%
“…Currently, therapeutic decisions are mainly based on primary tumor markers. However, several studies have shown a high degree of discordance between the primary tumor and metastatic sites or CTCs with respect to hormone receptor and HER2 expression (40)(41)(42)(43). Given the estimated short life span of CTCs in the circulation (44), the presence of CTCs in the peripheral blood of breast cancer patients after primary tumor resection suggests that the pool of CTCs is replenished by occult micrometastases.…”
Section: Discussionmentioning
confidence: 99%
“…Our study indicates the need for more comprehensive analysis of tissue and ctDNA NGS concordance beyond single genes and hotspot regions to determine utility and potential clinical applications of ctDNA biopsies. Interestingly, studies investigating concordance in biomarker expression between tissue analysis and CTCs, another component of liquid biopsies, have reported a lack of concordance between the two compartments with regards to hormone receptor and HER2 expression (36)(37)(38)(39). These findings clearly demonstrated phenotypic heterogeneity in both primary and metastatic breast cancer.…”
Section: Discussionmentioning
confidence: 99%